Development of Problem-Based Learning E-LKPD to Improve Mathematical Prob-lem-Solving Ability and Self-Confidence of High School Students on Quadratic Equations - Diah Lestari; Kana Hidayati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to: (1) produce e-LKPD based on problem-based learning oriented to mathematical problem-solving ability and self-confidence of high school students on the material of equations and quadratic functions and (2) describe the feasibility of PBL-based e-LKPD oriented to mathematical problem- solving ability and self-confidence of high school students on the material of equations and quadratic functions seen from the aspects of validity, practicality, and effectiveness. This type of research is research and development using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted at SMA Negeri 1 Malinau with the research subject of class X-3 students totaling 35 students. Data collection was carried out using interview techniques, observation, e-LKPD validation sheets, pretest-posttest, and questionnaires. To determine the validity, the e-LKPD assessment sheet of material and media experts was used, practicality used student and teacher response questionnaires, and effectiveness used mathematics problem solving ability test questions and student self-confidence questionnaires. Data analysis consisted of qualitative data analysis and quantitative data analysis. Qualitative data analysis was conducted by analyzing the results of interviews, observations, and comments or suggestions given to make improvements to the e-LKPD products developed. Quantitative data analysis was conducted by converting quantitative data into qualitative data in the form of certain categories, normality test using shapiro-wilk, t-test with paired samples test, and N-Gain score. The results showed: (1) PBL-based e-LKPDs oriented towards mathematical problem solving skills and self-confidence of high school students on the material of quadratic equations and functions have been produced, (2) PBL-based e-LKPDs developed meet product feasibility, namely valid with excellent categories based on material and media experts; practical with very practical categories based on teacher responses and practical based on student responses; effective on math problem solving skills with classical completeness of 77%, the t-test results obtained a significance value of 0.000 <0.05 which means that there is a difference in the average ability to solve mathematical problems before and after learning using e-LKPD, the N-Gain result is 0.65 with moderate criteria, and effective on student self-confidence with an increase in the average score of each indicator before and after learning, the N-Gain result is 0.49 with moderate criteria, and the t-test results with a significance value of 0.000 < 0.05.